2022
DOI: 10.1177/0271678x221078617
|View full text |Cite
|
Sign up to set email alerts
|

Defining cerebral leukocyte populations in local ischemic blood samples from patients with hyperacute stroke

Abstract: In acute stroke, neuroinflammation can nowadays be analyzed by local cerebral aspiration of pial-ischemic blood during mechanical thrombectomy. Recently, Shaw et al. reported on differences in leukocyte subpopulations within the occluded cerebrovascular compartment. In their study, a main proportion of granulocytes was lost during isolation. By immediate analysis, we found a reproducible increase in absolute local granulocytes without variations in absolute lymphocyte and monocyte numbers. Flow-cytometric phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“… 12 , 20 Flow cytometric automated detection and counting of leukocyte (sub-)populations again corroborated a strong predominance of neutrophils, and, in addition, disclosed a local shift in the relative distribution of lymphocytes towards CD4+ T-cells. 21 , 22 However, absolute lymphocyte numbers did not differ between local ischemic target and systemic control samples. Taken together these data indicated that LVO elicits a robust intravascular inflammatory response within the ischemic penumbra.…”
Section: The Local Neuroinflammatory Response In Human Hyper-acute St...mentioning
confidence: 89%
See 1 more Smart Citation
“… 12 , 20 Flow cytometric automated detection and counting of leukocyte (sub-)populations again corroborated a strong predominance of neutrophils, and, in addition, disclosed a local shift in the relative distribution of lymphocytes towards CD4+ T-cells. 21 , 22 However, absolute lymphocyte numbers did not differ between local ischemic target and systemic control samples. Taken together these data indicated that LVO elicits a robust intravascular inflammatory response within the ischemic penumbra.…”
Section: The Local Neuroinflammatory Response In Human Hyper-acute St...mentioning
confidence: 89%
“…While the relative proportion of CD4+ T-cells increased, the number of B-cells decreased. 21 , 22 Interestingly, immuno-deficient mice that lack any lymphocyte population are protected from progressive infarction under occlusion in the mouse pMCAO model 13 and also from I/R injury after recanalization 55 , 56 in the tMCAO model. This protection could be reversed in both models by adoptive transfer, particularly, of CD4+ T-cells among others.…”
Section: The Peculiar Role Of T-cells On Progressive Stroke Developmentmentioning
confidence: 99%
“…The immune‐biomarkers of stroke have drawn a lot of attention recently, such as lymphocyte, 30 neutrophil, 31 leukocyte, 32 monocytes, 33 T cell, 34 and et al Current literature on ULR is limited and restricted in patients after surgery. ULR was first proposed in the study of Wei et al, a retrospective study conducted in consecutive patients with rheumatic heart disease undergoing valve replacement surgery.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 However, in the following decades, reports on WBC came more frequently from patients with ischemic stroke. [14][15][16][17][18] One meta-analysis in 2021 indicated although confirms the association between WBC and unfavorable outcomes in aSAH patients, a strong conclusion cannot be made due to the limitation of the small study number, between-study heterogeneity, and suspicion of uncontrolled factors. 19 Therefore, whether WBC at admission can be regarded as a prognostic marker needs more investigation.…”
Section: Discussionmentioning
confidence: 99%